The Influence Of Product Quality And Product Design On Consumer Purchasing Decisions On CV. New Jaya Blessings Medan - Fadhylla, Ika; Harahap, Ahmad Taufiq; Firah, Al (Universitas Dharmawangsa Medan, 2024)
This research aims to find outthe influence of product quality and product design on consumer purchasing decisions at CV. Thanks to Jaya Baru Medan.This type of research uses quantitative research. The population of this study was 100 employees with a sample of 50 employees. The sampling technique uses the Slovin formula. Data analysis using multiple linear regression, the following results were obtained. HThe results of this research illustrate that there is a significant influence between product quality on consumer purchasing decisions at CV. Thanks to Jaya Baru Medan where the value of t > t table is 1.678 (8.498 > 1.678) in the positive direction. So Ha is accepted and H0 is rejected so it can be concluded that the product quality variable partially has a positive and significant effect on consumer purchasing decisions at CV. Thanks to Jaya Baru Medan. There is a significant influence between product design on consumer purchasing decisions at CV. Thanks to Jaya Baru Medan where the calculated t value < t table 1.678 (-1.637 < 1.678). So Ha is rejected and H0 is accepted so it can be concluded that partial product design has no effect and is not significant with a negative value on consumer purchasing decisions on CV. Thanks to Jaya Baru Medan.There isproduct quality and product design on consumer purchasing decisions at CV. Thanks to Jaya Baru Medan.